Modelling of crack propagation in miniaturized and normal SENB specimens based on local failure criterion (Fracture and Structural Integrity, 2024)
The use of miniaturized specimen testing methods is a promising way to solve the problem of limited materials in RPV monitoring programs. The use of miniature specimens allows the evaluation of fracture toughness from other specimen materials used. In particular, the small-size compact tensile test specimen (0.16T CT) is promising for the determination of fracture toughness, as it can be produced from the standard size Charpy specimen that has already been tested. However, if we have only 0.16T CT test, we cannot investigate the dimensional response and also have only one restricted deformation state, which may pose problems in verifying geometry independence and determining local parameters for state-of-the-art analyses. It is therefore recommended to prepare at least two tests with two different restricted deformation specimens. Therefore, the testing of mini single edge notched bending (SENB) is also required and can be worked out from the Charpy specimens. The paper presents the determination of fracture toughness for these miniaturized specimens by modifying the virtual crack closure technique (VCCT) simulation method using GTN parameters instead of energy release as the driving force. This allows the calculation of the J-integral to proceed in parallel with the crack propagation.
Keywords: GTN model; ANN method; VCCT (virtual Crack Closure Technique); Fracture toughness; Fracture mechanics